Analisis Pengaruh Kunjungan Wisatawan terhadap Perekonomian Kalimantan Selatan Melalui Penyerapan Tenaga Kerja - Syahrif, Airul (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
This study aims to analyze the effect of tourist visits on the economy of South Kalimantan through employment absorption from the perspective of the Tourism-Led Growth Hypothesis and Multiplier Effect Theory. It uses secondary time series data from 2011 to 2024 covering the number of tourist visits, employment absorption, and South Kalimantan's gross regional domestic product. This study applies path analysis to test the causal relationship between variables. The results show that tourist visits have a positive and significant effect on employment (β = 0.823; p < 0.001) and economic growth (β = 0.338; p = 0.001). Employment acts as a significant mediating variable (β = 0.560; p < 0.001). The role of labor mediation in transmitting the impact of tourism on the regional economy in South Kalimantan has not been widely explored in previous literature. These findings have important policy implications that the development of the tourism sector must be integrated with job creation strategies to maximize the multiplier effect on the regional economy.